Design of Soybean Epidermis Peeling Machine - Susilawati Susilawati; Masri Bin Ardin; Ferdi Fathurohman; Oyok Yudiyanto (VANOS Journal of Mechanical Engineering Education, 2023)
The process of stripping the soybean epidermis on tempe producers still uses the traditional method, namely by trampling the soybeans in the container until peeled. This causes the soybean to be crushed or split into two because the pressure exerted is unstable and unhygienic, need more time and effort. The aim of the study was to design a soybean epidermis peeler machine. The stages of the research were assessment, design, and validation design. The results of the research are machine designs with dimensions of length 505 mm, width 391 mm and height 815 mm with conventional pulley drives with crank manual working system and friction with capacity of 20 Kg/hour. The application of the machine soybean husk remover makes less effort is used and separation process of the skin from the soybean can be done more quickly so that it can increase production capacity.